Key science chemistry - Ramsden, Eileen ([S.l.] : Nelson Thornes Ltd, 1994)
Written for the co-ordinated science syllabuses under the National Curriculum, and for Science: Chemistry, this book has companion volumes on biology and physics. Topics are differentiated into core material for Double/Single Science and extension material for Science: Chemistry. These topics are linked to related ones in the companion volumes, but the links are optional, allowing this book to stand alone. A corresponding teacher's book and a resource bank are also available.
Keywords: chemistry